Impact of obesity and binge eating disorder on patients with idiopathic intracranial hypertension. (March 2017) - Raggi, Alberto; Curone, Marcella; Bianchi Marzoli, Stefania; Chiapparini, Luisa; Ciasca, Paola; Ciceri, Elisa FM; Erbetta, Alessandra; Faragò, Giuseppe; Leonardi, Matilde; D'Amico, Domenico
Background: Idiopathic intracranial hypertension (IIH) is associated with obesity, and obesity is associated with binge eating disorder (BED). The aim of this paper is to address the presence and impact of BED in patients undergoing an IIH diagnostic protocol. Methods: This was a cross-sectional study. Consecutive patients suspected of IIH underwent neurological, neuro-ophthalmologic and psychological examinations, neuroimaging studies and intracranial pressure (ICP) measurements through lumbar puncture in the recumbent position. IIH diagnosis was based on International Classification of Headache Disorders, 2nd Edition criteria; BED diagnosis was based on Diagnostic and Statistical Manual of Mental Disorders, 5th Edition criteria. The presence of oligoclonal bands (OCBs) in the cerebrospinal fluid was also assessed. Results: Forty-five patients were enrolled: 33 were diagnosed with IIH and five of them (15%) were obese with BED. Compared to non-obese patients, those who were obese, and particularly those who were obese with BED, were more likely to have an IIH diagnosis (χ 2 = 14.3; p = 0.001), ICP > 200 mmH2 O (χ 2 = 12.7; p = 0.002) and history of abuse or neglect (χ 2 = 11.2; p = 0.004). No association with OCBs was found. Conclusions: We reported for the first time the presence of BED among patients with IIH and showed that BED is associated to IIH, ICP and history of abuse or neglect.